Intracellular Pathogen Leishmania donovani Activates Hypoxia Inducible Factor-1 by Dual Mechanism for Survival Advantage within Macrophage - Singh, Amit Kumar (Public Library of Science, 2012)
Recent evidence established a crucial role for mammalian oxygen sensing transcription factor hypoxia inducible factor-1 (HIF-1) in innate immunity against intracellular pathogens. In response to most of these pathogens host phagocytes increase transcription of HIF-1α, the regulatory component of HIF-1 to express various effector molecules against invaders. Leishmania donovani (LD), a protozoan parasite and the causative agent of fatal visceral leishmaniasis resides in macrophages within mammalian host. The mechanism of HIF-1 activation or its role in determining the fate of LD in infected macrophages is still not known. To determine that J774 macrophages were infected with LD and about four-fold increase in HIF-1 activity and HIF-1α expression were detected. A strong increase in HIF-1α expression and nuclear localization was also detected in LD-infected J774 cells, peritoneal macrophages and spleen derived macrophages of LD-infected BALB/c mice. A two-fold increase in HIF-1α mRNA was detected in LD-infected macrophages suggesting involvement of a transcriptional mechanism that was confirmed by promoter activity. We further revealed that LD also induced HIF-1α expression by depleting host cellular iron pool to affect prolyl hydroxylase activity resulting in to stabilization of HIF-1α. To determine the role of HIF-1 on intracellular LD, cells were transfected with HIF-1α siRNA to attenuate its expression and then infected with LD. Although, initial infection rate of LD in HIF-1α attenuated cells was not affected but intracellular growth of LD was significantly inhibited; while, over-expression of stabilized form of HIF-1α promoted intracellular growth of LD in host macrophage. Our results strongly suggest that LD activates HIF-1 by dual mechanism for its survival advantage within macrophage.